PENERAPAN WIRELESS COMUNICATION HC-05 PADA MODEL KENDALI ECOSYSTEM (EVAPORATIVE COOLER SYSTEM) - Rizka Amalia; Reni Rahmadewi; Dian Budi Santoso (Politeknik Harapan Bersama Tegal, 2021)
Abstract The interconnectedness of the times includes all aspects, one of which is the temperature of the earth which is getting warmer, the annual prediction of increasing by 1 ° to 1.5 ° Celsius. In addition, there are technological updates with ideas that are a daily necessity. Evaporative Cooler is a conventional air conditioner throughout the world with various types and types, DEC (Direct evaporative Cooler), for example works by converting sensible heat into latent heat, whose main circuit consists of an electric motor, swing cooler motor and 24V DC water pump, a actuator module used in the implementation of this system. The idea that came up was that not many people paid attention to the system its use. This research will apply one of the wireless communication, namely the Bluetooth HC-05 Module in the control model design using ECOSYSTEM (Evaporative Cooler System) where the input is integrated with an artificial application installed on a smartphone with Bluetooth devices in it with the android operating system so that it can communicate between systems. Focusing on the communication performance applied by the HC-05 with a 2.4GHz frequency as a receiver or sender of commands with a range of signal distances that can be given, equipped with an Arduino UNO ATMega328 microcontroller for core system controllers. Over-the-air communication model that does not require other media devices in the process of working. Measurement of the performance of the signal coverage is proven horizontally and vertically, intended because there is a difference in the capture power of the transceiver and receiver signals as well as the conditions when bluetooth is controlled, it is connected and not yet connected. In the test, bluetooth only captures two conditions when it is working, when it is still affordable, bluetooth will connect and remain connected with a delay of not more than 0.02 seconds or not connected at all when the range is getting farther.